Cross section asymmetry of the ¹²C(γ→,p0)¹¹B and ¹²C(γ→,p1)¹¹B reactions at photon energies 40...55 MeV - Burdeinyi, D.D.; Brudvik, J.; Ganenko, V.B.; Hansen, K.; Fissum, K.; Livingston, K.; Isaksson, L.; Lundin, M.; Nilsson, B.; Schröder, B. (Вопросы атомной науки и техники, 2019)
The asymmetry of the cross section of the ¹²C(γ→,p0)¹¹B and ¹²C(γ→,p1)¹¹B reactions has been measured in the energy range 40...55 MeV using linearly polarized tagged photons of the MAX-lab facility. The asymmetry of the process ¹²C(γ→,p0)¹¹B is Σ ≈ 0.85, that implies one-particle reaction mechanism. The asymmetry of the reaction ¹²C(γ→,p1)¹¹B is smaller, Σ ≈ 0.6...0.7, that may be due to the stronger relative contribution of the 2h−1p mechanism to the dominant one-particle reaction mechanism. Асиметрія перерізу ¹²C(γ→,p0)¹¹B і ¹²C(γ→,p1)¹¹B реакцій була виміряна на пучку лінійно-поляризованих мічених фотонів на МАХ-лаб установці в інтервалі енергій 40...55 МеВ. Показано, що асиметрія процессу ¹²C(γ→,p0)¹¹B дорівнює Σ ≈ 0.85, що вказує на одночастковий механізм реакції. Асиметрія перерізу реакції ¹²C(γ→,p1)¹¹B менше, Σ ≈ 0.6...0.7, що може бути пов'язано з більш сильним відносним внеском механізму 2h-1p в домінуючий одночастковий механізм реакції. Асимметрия сечения ¹²C(γ→,p0)¹¹B и ¹²C(γ→,p1)¹¹B реакций была измерена на пучке линейно-поляризованных меченных фотонов на МАХ-лаб установке в интервале энергий 40...55 МэВ. Показано, что асимметрия процесса ¹²C(γ→,p0)¹¹B равна Σ ≈ 0.85, что соответствует одночастичному механизму реакции. Асимметрия сечения реакции ¹²C(γ→,p1)¹¹B меньше, Σ ≈ 0.6...0.7, что может быть связано с более сильным относительным вкладом механизма 2h-1p в доминирующий одночастичный механизм реакции.